Strategic digital shipbuilding project portfolio configuration and optimisation. (5th October 2022) - Diaz, Rafael
Program portfolio managers in digital transformation projects need knowledge that can guide allocation decisions associated with the configuration of project assets within the sustainable and strategic objectives of the firm. This research aims to propose a framework capable of optimising the cost-benefit adjustments from assessing investment risks of digital transformation projects such as cybersecurity projects. The context considers the innovative sector of military shipbuilding and repair. Our approach uses an artificial neural network (ANN) and Monte Carlo simulation modelling to capture risk effects and quantify investment priorities. This method enables the application of portfolio management theory principles to measure and optimise the performance of the digitalisation project portfolio. The framework's utility is discussed using a hypothetical case study presenting several digital transformation project investment scenarios.